Comparative Study of Combustion Properties of Two Seaweeds in a Batch Fluidized Bed. Issue 5 (4th May 2018) - Wang, Shuang; Cao, Bin; Abomohra, Abd El-Fatah; Hu, Yamin; Wang, Qian; He, Zhixia; Xu, Shannan; Feng, Yongqiang; Bernard, Uzoejinwa Benjamin; Jiang, Xiumin
ABSTRACT: In the present study, combustion of two seaweeds, Enteromorpha clathrate and Sargassum natans, was carried out in a bench-scale fluidized bed. According to the shrinking core model, combustion of E. clathrate particles resulted in dehydration and release of volatile components first, followed by char combustion. While combustion of S. natans particles resulted in scraps formation due to the rapid release of large amounts of volatiles, followed by expansion and fragmentation. The cross sections of E. clathrate particles and the cokes collected after different combustion durations were analyzed with a scanning electron microscope. Some micro-pores were generated with a rougher surface after being burned for 30 s. When combustion continued for 3 min, a cotton wool-like structure was obtained due to complete release of volatiles. After 4 min of burning, internal surface of the ash particle became cohesive, due to partial melting of ash particles. In addition, the released gases were studied during the combustion process. Results showed that SO2, NOx, and other gases emitted spontaneously as soon as seaweed particles were fed into the fluidized bed, indicating that both pyrolysis and oxidation reactions rapidly take place within the seaweed particles. In general, the heat transfer rate was accelerated by increasing bed temperature and led to an earlier release of volatile components with shortened burnout time. Moreover, increasing air velocity and raising the bed height also enhanced, to some extent, the combustion and shortened the burnout time.